Invertebrate and vertebrate predation rates in a hyperarid ecosystem following an oil spill. Issue 17 (13th August 2021) - Ferrante, Marco; Möller, Daniella; Möller, Gabriella; Menares, Esteban; Lubin, Yael; Segoli, Michal
Abstract: Extreme temperatures and scarce precipitation in deserts have led to abiotic factors often being regarded as more important than biotic ones in shaping desert communities. The presumed low biological activity of deserts is also one reason why deserts are often overlooked by conservation programs. We provide the first quantification of predation intensity from a desert ecosystem using artificial sentinel prey emulating caterpillars, a standardized monitoring tool to quantify relative predation pressure by many invertebrate and vertebrate predators. The study was conducted in a protected natural area affected by oil spills in 1975 and 2014; hence, we assessed the potential effects of oil pollution on predation rates. We found that predation was mostly due to invertebrate rather than vertebrate predators, fluctuated throughout the year, was higher at the ground level than in the tree canopy, and was not negatively affected by the oil spills. The mean predation rate per day (12.9%) was within the range found in other ecosystems, suggesting that biotic interactions in deserts ought not to be neglected and that ecologists should adopt standardized tools to track ecological functions and allow for comparisons among ecosystems. Abstract : Extreme environments such as deserts are expected to have low biodiversity and, therefore, reduced biotic interactions. We addressed this assumption by measuring invertebrate and vertebrate predation rates in a hyper‐arid desert using a standardized monitoring tool that allows recording predator activity in a quantitative, comparable way. We found that the mean predation rate (12.9% per day) is within the range found in other ecosystems, suggesting that this biotic function is no less important in deserts than elsewhere.